The degree of primary third-class female teachers’ practice of raising questions of higher mental skills in teaching listening - Ajaj, Muneer; Alomyan, Hesham (International Journal of Innovative Research and Scientific Studies, 2025)
The current study aims at unveiling the degree of how primary third-class female teachers practice posing the questions that address students’ higher mental skills when teaching listening. The study sample consists of randomly-selected 35 third-class female teachers who have worked in primary schools of Private Education Department. The two researchers, in attempt to achieve the study aims objectively, adopt the observation-based instrument. The statistical results elucidate that female teachers, namely the study sample are of the opinion that lower mental skills, i. e. analysis and application play a leading role and represent a prominent stage through which higher mental skills, i.e. synthesis and evaluation are chiefly acquired. The researchers think that the Arabic language courses of the third classes provide more focus on analysis and application than synthesis and evaluation and this, in turn, contributes to female teachers’ feeling to adopt the former skills rather than the latter ones. In addition, when applied, synthesis and evaluation require more allotted time and more exerted efforts than those of lower skills.